Utilização do endocarpo da macaúba como agregado graúdo alternativo para a produção de bio-concretos - Andrade, Gabriele Melo de (2022)
Macaúba (Acrocomia aculeata (Jacq.) Lodd. ex Mart.) is a palm tree with an oleaginous fruit which endocarp may have potential as an alternative aggregate to produce bio-concretes.This paper proposes a study of the characteristics of the endocarp of macaúba, to evaluate its potential and behavior as a coarse aggregate in bio-concretes. The endocarp used for the study was provided by the Engineering Department of the Federal University of Lavras (UFLA), located in Lavras, MG, Brazil. The endocarps were characterized as to its chemical composition, anatomical characteristics, physical properties and durability in alkaline conditions The chemical compatibility between the endocarp and the cement matrix was evaluated by semi-adiabatic calorimetry analysis with macauba endocarp treated and untreated with Ca(OH)2 and hot water in a proportion of 10% in relation to the cement mass. Bio-concretes were developed using Portland cement (CP- V ARI), with substitutions in mass and volume of 25, 50 and 100% of coarse aggregate by macauba endocarp. The bio-concretes were mechanically characterized by axial compression and tensile tests by diametrical compression. The results showed that the endocarp has a bulk density of 1.23 g/cm3 and an absorption capacity of 9%. Chemical analysis showed a high lignin content (39.60%) and low extractive content (3.10%). The durability of the endocarp was more compromised in the presence of alkaline NaOH solution after 30 and 60 days, with a decrease in mechanical strength and modification of the chemical composition of the material. The hot water treatment was more efficient in removing extractives from the endocarp and improving the chemical compatibility with the matrix. The addition of 25% of the volume of coarse aggregate by macauba endocarp provided a bio- concrete with compressive strength of approximately 30 MPa, within the strength range required for application as structural concrete in civil construction.